Kajian Metode Pelaksanaan Dan Biaya Instalasi Pengolahan Lumpur Tinja Di Boyolali Studi kasus Peningkatan Bangunan Pengolah Lumpur Tinja Nomor Paket PPLP AL BYL 01 di Kabupaten Boyolali - Gunarso, Mr, Dr. Ir. Sri Sunarjono, M.T, Ir. M. Nur Sahid, M.T., M.M (2015)
Every day people throw dirt from her body, and every day do people bathe, wash and so forth so as to produce food sisa2 dirt. In other words, household waste (domestic waste water) with waste directly into the river / times continuously it will disturb / damage laingkungan, hence the need to build a waste treatment plant, with the aim to reduce levels of BOD, COD and bacteria Coli and sat other suspended , So that the leakage problems that often arise as a result of not fulfilling relationship between the density of the surface of old concrete casting stage to the next stage casting concrete surfaces. To resolve this issue done by using waterstop as a cap for water. This study aims to determine and develop methods of evaluating the implementation of sludge treatment in Boyolali. Approaches and methods of implementation of this research is supported by quantitative descriptive qualitative data. The sampling method used was cluster sampling and purposive sampling combined. Based on the results of the study can be summarized as follows that the implementation of development IPLT in Boyolali consists of several stages, including Preparation Work, Building Work Bak Gatherer, Swimming Anaerobic, Facultative pond Building Works 1.2, Works maturation pond Building, Building Work Slug drying bed, Building pool Wet Land, Mecanikal electrical and Environmental Way. In the implementation of the WWTP project happen constraints such as the addition of bamboo and aerators Trucuk jobs that do not exist in the RAB so that the need for additional work, where every additional aerator has an impact on costs. Aerator function is very important to reduce the content of BOD / COD, E Coli and other suspended substances. Evaluation is done by comparing the cost of calculation ACWP, BCWP, and BCWS then obtained by calculating the difference between the results of 9.863%